Pengaruh Kepemimpinan Kepala Madrasah Dan Budaya Religius Terhadap Mutu Pembelajaran Di MAS Al Washliyah 22 Tembung - Abdul Lathif Sitompul; Muhammad Rifai (JURNAL MANAJEMEN PENDIDIKAN, 2026)
The Influence of Madrasah Head Leadership and Religious Culture on the Quality of Learning in Mas Al Washliyah 22 Tembung This study aims to analyze the influence of the madrasa head's leadership and religious culture on the quality of learning at MAS Al Washliyah 22 Tembung. This research used an associative quantitative method with data collection through questionnaires distributed to 32 teacher respondents. Data analysis was performed using multiple linear regression processed via SPSS software. The results show that: (1) The madrasa head's leadership has a positive and significant influence on the quality of learning; (2) Religious culture has a positive and significant influence on the quality of learning; (3) Simultaneously, both variables significantly influence the improvement of learning quality, with a coefficient of determination (R^2) of 64.1%. These findings imply that strengthening participatory leadership styles and maintaining consistency in building a religious culture are strategic keys to improving the quality of the learning process sustainably.